Los precios en la nueva síntesis neoclásica-keynesiana en macroeconomía - Alexander Tobón (Lecturas de Economía, 2008)
The aim of this paper is to study the role that prices play in the New Neoclassical Synthesis. It is shown that although the New Synthesis emphasizes the importance of having a monetary theory to recommend monetary policies, it essentially offers the same answers on the minor role of prices in static macroeconomics. In spite of this, the New Neoclassical Synthesis has the merit of attempting to return to the pre-Keynesian intuitions of Wicksell, which indeed could contribute to the search for not just better answers, but for new questions regarding prices in a monetary theory.